Analisis dan Perencanaan Pencahayaan Buatan pada Toko Kelontong Menggunakan DIAlux Evo 12.0 - Ahmad Yusif; Riana Defi Mahadji Putri; Muhammad Harlanu; Tatyantoro Andrasto (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
A grocery store must consider the comfort of people engaging in activities within it, one of which is lighting. Good lighting is an essential part of visual comfort. According to SNI 6197:2020, the standard illumination level for grocery stores is 300 lux. However, initial measurements revealed that during nighttime, the illumination level in the grocery store did not meet the standard, with an average measured illumination level of only 35 lux. Based on this issue, this study aims to determine the appropriate lighting design for grocery stores through analysis using the DIAlux EVO 12.0 software. This research employs the ADDIE research and development model, which comprises five stages: analysis, design, development, implementation, and evaluation. The results of the study, following development using the DIAlux EVO 12.0 software, indicate that five lighting points are required in the grocery store using Philips LED Bulb 19-watt Cool Daylight lamps. After implementation, re-measurements showed that the average nighttime illumination level reached 308 lux. Therefore, the research and development on lighting levels in the grocery store can be considered successful, as it significantly improved lighting in areas or conditions with illumination levels below the Indonesian National Standard.